Simulation Analysis of Base Year Operation Pattern Method of Marangkayu Reservoir East Kalimantan Province - Gonzales Sihite; Hari Nugroho (TEKNIK, 2025)
Marangkayu is a multi-purpose dam that serves irrigation water needs for a functional area of 1,500 hectares and provides raw water supplementation of approximately 450 liter per second. One of the requirements for impounding certification involves the preparation of an operational guideline for the dam. Therefore, this study aims to analyze the reservoir operation pattern by simulating water availability and demand. The reservoir operation pattern is determined through simulations based on calculations of water inflow, water demand, and losses, constrained by the reservoir's storage capacity. The simulation calculations employ the baseline year method, which includes dry years, normal years, and wet years. Reservoir water availability simulations are conducted under three conditions: dry year (probability of being equaled or exceeded 65%), normal year (probability of being equaled or exceeded 50%), and wet year (probability of being equaled or exceeded 35%). The results of this study indicate that the simulation of Marangkayu reservoir's operation pattern for dry, normal, and wet conditions can sufficiently meet the water needs for a functional irrigation area of 1,500 hectares with a cropping pattern of rice–rice–secondary crops, raw water demand of 450 liter per second, and river maintenance flow of 0.848 m³/second.